Identification of Lactate as a Cardiac Protectant by Inhibiting Inflammation and Cardiac Hypertrophy Using a Zebrafish Acute Heart Failure Model - Elijah R. Haege; Hui-Chi Huang; Cheng-chen Huang (MDPI AG, 2021)
Acute heart failure (AHF) commonly arises from decompensated chronic heart failure or sudden structural and functional breakdown causing a decrease in cardiac contractility and consequently fluid accumulation and systemic congestion. Current treatment for AHF aims at reducing fluid overload and improving hemodynamic which results in quick symptom relief but still poor prognostic outcome. This study utilizes a zebrafish AHF model induced by aristolochic acid (AA) to look for natural products that could attenuate the progression of AHF. The project started off by testing nearly seventy herbal crude extracts. Two of the positive extracts were from Chinese water chestnuts and are further studied in this report. After several rounds of chromatographical chemical fractionation and biological tests, a near pure fraction, named A2-4-2-4, with several hydrophilic compounds was found to attenuate the AA-induced AHF. A2-4-2-4 appeared to inhibit inflammation and cardiac hypertrophy by reducing MAPK signaling activity. Chemical analyses revealed that the major compound in A2-4-2-4 is actually lactate. Pure sodium lactate showed attenuation of the AA-induced AHF and inflammation and cardiac hypertrophy suppression as well, suggesting that the AHF attenuation ability in A2-4-2-4 is attributable to lactate. Our studies identify lactate as a cardiac protectant and a new therapeutic agent for AHF.